Coal consumption, CO2 emission and economic growth in China: Empirical evidence and policy responses - Bloch, Harry; Rafiq, S.; Salim, Ruhul (Elsevier, 2011)
This article investigates the relationship between coal consumption and income in China using both supply-side and demand-side frameworks. Cointegration and vector error correction modeling show that there is a unidirectional causality running from coal consumption to output in both the short and long run under the supply-side analysis, while there is also a unidirectional causality running from income to coal consumption in the short and long run under the demand-side analysis. The results also reveal that there is bi-directional causality between coal consumption and pollutant emission both in the short and long run. Hence, it is very difficult for China to pursue a greenhouse gas abatement policy through reducing coal consumption. Switching to greener energy sources might be a possible alternative in the long run.